Survey of planetesimal belts with ALMA: gas detected around the Sun-like star HD 129590. Issue 3 (11th July 2020) - Kral, Quentin; Matrà, Luca; Kennedy, Grant M; Marino, Sebastian; Wyatt, Mark C
ABSTRACT: Gas detection around main-sequence stars is becoming more common with around 20 systems showing the presence of CO. However, more detections are needed, especially around later spectral type stars to better understand the origin of this gas and refine our models. To do so, we carried out a survey of 10 stars with predicted high likelihoods of secondary CO detection using ALMA in band 6. We looked for continuum emission of mm-dust as well as gas emission (CO and CN transitions). The continuum emission was detected in 9/10 systems for which we derived the discs' dust masses and geometrical properties, providing the first mm-wave detection of the disc around HD 106906, the first mm-wave radius for HD 114082, 117214, HD 15745, HD 191089, and the first radius at all for HD 121191. A crucial finding of our paper is that we detect CO for the first time around the young 10–16 Myr old G1V star HD 129590, similar to our early Sun. The gas seems colocated with its planetesimal belt and its total mass is likely in the range of (2–10) × 10 −5 M⊕ . This first gas detection around a G-type main-sequence star raises questions as to whether gas may have been released in the Solar system as well in its youth, which could potentially have affected planet formation. We also detected CO gas around HD 121191 at a higher signal-to-noise ratio than previously and find that the CO lies much closer-in than the planetesimals in the system, which could be evidence for the previously suspected CO viscous spreading owing to shielding preventing its photodissociation. Finally, we make estimates for the CO content in planetesimals and the HCN/CO outgassing rate (from CN upper limits), which we find are below the level seen in Solar system comets in some systems.